Soybean meal and poultry offal meal effects on digestibility of adult dogs diets: Systematic review. - Karoline Vanelli; Angela Cristina Fonseca de Oliveira; Cristina Santos Sotomaior; Saulo Henrique Weber; Leandro Batista Costa (PLoS ONE)
Soybean meal and poultry offal meal are protein ingredients commonly used in the formulation of commercial diets for dogs. However, there remains great variability in the data on the digestibility of each protein source. This systematic review study aimed to examine the intake, apparent nutrient digestibility coefficients and fecal output of protein sources (soybean meal and poultry offal meal) in adult dog food as reported in published studies. The article search was conducted in August 2018 in the PUBMED, SciELO, Science Direct and AGRIS indexing databases. The literature search was performed using "digestibility", "source protein" and "dog" as the main key terms combined with sub-terms to broaden the scope of the search. Criteria were defined for readability, exclusion and inclusion of articles. Results were organized in groups according to the search in the indexing databases, totaling 1,414 articles. After the works were selected following the inclusion criteria, 17 articles were evaluated in this review. According to most studies, plant-based ingredients have a less variable nutritional composition than animal-derived ingredients and poultry offal meal increases the digestibility coefficients of nutrients and energy and reduces fecal dry matter production. Factors inherent to raw-material origin, ingredient and food processing, as well as the high heterogeneity of the methodologies evaluated in the studies are directly related to the obtained results. To ensure a more accurate evaluation of the quality and of effects on the digestibility of protein sources, we recommended that articles include ingredient processing data and that the variables be evaluated under standardized study conditions.